2015
DOI: 10.1292/jvms.15-0188
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of clothianidin and environmental stress on the behavioral and reproductive function in male mice

Abstract: Neonicotinoids, some of the most widely used pesticides in the world, act as agonists to the nicotinic acetylcholine receptors (nAChRs) of insects, resulting in death from abnormal excitability. Neonicotinoids unexpectedly became a major topic as a compelling cause of honeybee colony collapse disorder, which is damaging crop production that requires pollination worldwide. Mammal nAChRs appear to have a certain affinity for neonicotinoids with lower levels than those of insects; there is thus rising concern abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 42 publications
(45 reference statements)
1
68
0
Order By: Relevance
“…Similar significant behavioral effects were detected with exposure to nicotine (Crosby et al 2015). Other studies using mice have also found effects on anxiety behaviors with exposure to clothianidin or acetamiprid, but in these studies anxiety was either increased (Hirano et al 2015) or decreased (Sano et al 2016). It is possible that the frogs may be highly anxious and resort to the preferred cryptic response instead of the less preferred flight response or have reduced anxiety and thus do not feel the need to flee.…”
Section: Discussionmentioning
confidence: 67%
“…Similar significant behavioral effects were detected with exposure to nicotine (Crosby et al 2015). Other studies using mice have also found effects on anxiety behaviors with exposure to clothianidin or acetamiprid, but in these studies anxiety was either increased (Hirano et al 2015) or decreased (Sano et al 2016). It is possible that the frogs may be highly anxious and resort to the preferred cryptic response instead of the less preferred flight response or have reduced anxiety and thus do not feel the need to flee.…”
Section: Discussionmentioning
confidence: 67%
“…However, increasing evidence to the contrary [11,12,13,14,15,16,17,18,19], and consideration of some neonicotinoid metabolites showing high affinities for mammalian nAChRs [3], suggests that neonicotinoids have potential developmental neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the neonicotinoids thiamethoxam and clothianidin induced dopamine release in the rat striatum via nAChRs [12] and thiamethoxam altered behavioral and biochemical processes related to the cholinergic systems in rat [13]. Gestational administration of clothianidin induces behavioral disorders in F1 mice [14] and exposure to clothianidin and other stress causes behavioral and reproductive abnormalities in male mice [15]. Exposure to IMI alters learning performance and related gene expression in infant and adult rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of gestating mice to clothianidin also reduced germ cell count in the offspring without hormonal changes (126). Still in mice, Hirano et al (127) reported clothianidin-induced behavioural and reproductive effects, which were more pronounced under chronic stress. Treatment of mouse embryos with 1000 µmol L -1 of thimaetoxam, clothianidin, acetamiprid, and thiacloprid during the preimplantation period had negative effects on embryo developmental abilities (128).…”
Section: Neonicotinoid Effects On Vertebratesmentioning
confidence: 94%